The effect of cover crops and P management strategies on soil physical properties and soil organic carbon - Stahl, Kendra (Kansas State University, 2023)
Cover crops and no-till have been demonstrated to improve soil physical properties and soil organic carbon. However, there has been less research on phosphorus fertilizer timing and placement effects on soil physical properties and soil organic carbon. The Kansas Agricultural Watershed (KAW) field laboratory near Manhattan, Kansas was established in 2014. The soil at the site is mapped as a Smolan silty clay loam with 6-8% slope. The experiment was a 2 × 3 factorial design with two cover crop treatments (cover and no cover) and three phosphorus fertilizer treatments (none, spring injected P, and fall broadcast P). The field lab contains 18 plots about 0.49 hectares each, each containing 3 subplots sampled. It has been hypothesized that cover crops will enhance soil physical properties (increase water stable aggregates, and decrease bulk density), increase soil organic carbon, and assist in the uptake of phosphorus fertilizer. Water stable aggregate samples were collected for the 0 to 5 and 5 to 10 cm depths in 2017, 2018, 2019, and 2022. Bulk density and total carbon were sampled at 0 to 5 cm and 5 to 10 cm in the spring of 2022. Aggregate data showed an overall trend of cover crops increasing aggregation compared to no cover treatments. The size fractions between each year increase in size over time. Bulk density was found to be around 1.1 g cmˉ³ at the surface depth, while the subsurface depth is denser, approximately 1.3 g cmˉ³, which is less than 1.55 g cmˉ³, a density that is considered root-restrictive for silty clay loam soil textures. Total carbon results differed with cover crop management, however, there were no differences when converted to a mass per unit area basis (Mg ha⁻¹). Since the site has a pronounced slope, we also tested if the soil texture differed across the slope. Although there were points on the landscape where the clay content differed by ±15%, this difference did not have an impact on any of the variables measured for our treatments. The P management strategies had no effects on the physical soil properties; thus, we conclude that cover cropping is the main factor responsible for enhancing soil physical properties at the KAW field laboratory.
Keywords: Cover crop; P management; Soil organic carbon